A review of the subgenera Euorthocladius and Orthocladius s. str. from China (Diptera: Chironomidae) - Kong, Fanqing; Sæther, Ole A.; Wang, Xinhua (Zootaxa, 2012)
The Chinese species of the subgenera Euorthocladius Thienemann and Orthocladius s. str. are reviewed. Two new species of Orthocladius (Euorthocladius): O. (E.) angustus and O. (E.) flectus are described, and four species of Orthocladius s. str. are redescribed and illustrated as adult males. A key to males of the two subgenera from China is presented.